THREATS TO U.S. CONTROL OF MIDDLE EASTERN OIL - Aijaz Ahmad Wani (CV. Radja Publika, 2023)
Since the discovery of oil wealth in the region of Middle East it became the battle ground for great States to compete on. Particularly after the world war 2ndtill this date the great states like Britain, France, Russia and China are early watching the chessboard to manipulate an opportunity in their favour. It is this competition over the oil of Middle East which has left the control of America both insecure and competitive.